La representación de la mujer venezolana en redes sociales peruanas a través del término veneca - Prado Ishuiza, Cesar Alberto (2021)
In Latin America today, Venezuelan migration has become a political, economic, cultural and social problem. In this sense, in the Peruvian territory, migratory waves have led to the establishment of measures to assist Venezuelans fleeing the crisis in their country; on the other hand, social networks have contributed to form a stigmatized image of the migrant. This paper aims to analyze the discourse of social network users regarding the representation of Venezuelan women through the pejorative term veneca. Methodologically, comments are collected on Facebook and Twitter during the month of June 2021. Finally, it is concluded that Venezuelan women are represented negatively based on the generally prejudiced images attributed to them by Peruvian cybernauts.